The domain-specificity of serial order working memory. - Tian, Yingxue; Beier, Margaret E.; Fischer-Baum, Simon (Memory & Cognition, 2022)
Making a turn while driving is simple: turn on the indicator, check for cars, then turn. Two types of information are required to perform this sequence of events: information about the items (e.g., the correct indicator), and the serial order of those items (e.g., checking before turning rather than vice-versa). Previous research has found distinct working memory capacities (WMCs) for item and serial order information in both verbal and nonverbal domains. The current study investigates whether the serial order WMC is shared for sequences from different content domains. One hundred and fifty-three participants performed sequence matching tasks with verbal (letters and words) and nonverbal (locations and arrows) stimuli. The accuracy of detecting mismatched item-identity and serial order information in sequences was used to operationalize item and order WMC. Using structural equation modeling analyses, we directly compared models that included either domain-specific or domain-general serial order WMC latent variables, finding that models with domain-specific serial order WMC latent variables for verbal and nonverbal materials fit the data better than models with domain-general latent variables. The findings support the hypothesis that there are separate capacities for serial order working memory depending on the type of material being ordered.